Digital intelligence technology and curriculum ideology in sports colleges: the mediating roles of teaching effectiveness and student engagement - Wang, Ziqi; Bu, Xiangui; Hong, Siyu; Jia, Zixuan; Huang, Zeqi; Wang, Wenjun (Frontiers in Education, 2025)
IntroductionThis study explores the role of digital intelligence technology (DIT) in indirectly enhancing curriculum ideological effectiveness in sports colleges through improvements in teaching effectiveness and student engagement. The research provides insights into how technology integration can influence ideological and political education outcomes.MethodsA nationwide sample of 804 faculty and student respondents was analyzed using a chain mediation model grounded in the Technology Acceptance Model, Self-Determination Theory, and Educational Ecosystem Theory. Structural Equation Modeling (SEM) was applied to examine the relationships between DIT, teaching effectiveness, student engagement, and curriculum ideology outcomes.ResultsThe findings reveal that DIT significantly enhances teaching effectiveness and student engagement, which sequentially contribute to improved curriculum ideology outcomes. Student engagement accounted for a greater proportion of variance compared to teaching effectiveness, emphasizing the critical role of interactive learning in ideological and political education.DiscussionThis study introduces a novel chain mediation pathway—DIT → Teaching Effectiveness → Student Engagement → Curriculum Ideology—highlighting the synergistic relationship between teaching quality and learner participation. The findings provide theoretical contributions to understanding technology integration in sports education and practical recommendations for professional development and interactive classroom practices to optimize the impact of DIT.